Ice hockey teams in four olympic games: analysis of age and anthropometric characteristics - Samsonova, A. V.; Mikhno, L. V.; Chichelov, I. A. (Theory and Practice of Physical Culture, 2019)
The study was designed to make an age-specific anthropometric characteristics (body length and body mass) analysis of the six ice hockey teams (n=580) that competed in the last four Olympic Games in Turin (2006), Vancouver (2010), Sochi (2014) and PyeongChang (2018). It was found that the offense and defense pools may be provisionally classified by their anthropometric characteristics into the attack-only and offense-and-defense specialized offense subgroups; and the defense-only and defense-and-offense defense subgroups.